An objective study into the effects of an incline on naturally occurring lameness in horses. Issue 6 (18th August 2022) - Bailey, James; Redpath, Adam; Hallowell, Gayle; Bowen, Mark
Abstract: Background: The clinical examination of lame horses in real world settings often requires the use of sloped surfaces. Objectives: This pilot study aimed to evaluate the effects of uphill and downhill locomotion on asymmetry in horses with naturally occurring lameness affecting forelimbs and hindlimbs. Methods: Ten horses (8–19 years) with forelimb lameness and eight horses (7–16 years) with hindlimb lameness were fitted with inertial sensors at the poll, withers, sacrum and both tuber coxae. Data were collected whilst the horses were trotted in hand on a level surface (<0.7%), as well as up and down a minor slope of 2.4%. Data were collected for a minimum of 25 strides at each incline type. Effect of incline was compared using a repeated measures ANOVA and, where significant, a subsequent Bonferroni's multiple comparisons. Results: Of the horses with hindlimb lameness, there were reductions in asymmetry seen during downhill locomotion when compared with trotting on the flat (flat: 6.6 ± 4.4 mm to downhill: 1.9 ± 2.9 mm; p = 0.015) and when compared with uphill locomotion (8.4 ± 4.3 mm; p = 0.007). Horses with forelimb lameness showed no significant difference in asymmetry. However, there were considerable changes in poll asymmetry (>20 mm) among conditions in individual horses. Two horses with hindlimb lameness and two horses with forelimb lameness switched asymmetry between left and right by changing incline. Conclusions: These results confirm that incline can be an influential factor in the assessment of lame horses. Further work is justified to elucidate the types of pathology associated with the most relevant changes in asymmetry which would allow the use of an incline to prioritise a list of differential diagnoses. Abstract : The clinical examination of lame horses in real world settings often requires the use of imperfect surfaces. This study identifies significant differences in the sacral asymmetry of mildly hindlimb lame horses trotting down a slope when compared to on a flat or uphill surface and also shows the large variability of poll asymmetry in horses with forelimb lameness between the test conditions.